Effects of relative humidity on the development of Nabis punctatus Costa (Rhynchota Nabidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Trials were carried out to evaluate the influence of different levels of relative humidity on the pre-imaginal time of development and mortality, on the number of eggs each female lays, and on the lifetimes of the adults (males and females). As far as the adult female's lifetime is concerned, a separate analysis was made of three periods, based on oviposition activity: the period between emergence of the adult and the beginning of oviposition, the period of oviposition, and the period from the end of oviposition and death. Relative humidity has been shown to influence significatively some important life parameters of the species.
Keywords: Nabis punctatus; relative humidity; oviposition; development; rearing